การจัดทำตัวชี้วัดการจัดการทรัพยากรและแนวปฏิบัติของสหกรณ์โรงอบ/รมยางแผ่น - สุเมธ ไชยประพัทธ์ (มหาวิทยาลัยสงขลานครินทร์)
In 1993, the central government had allocated funding and assigned the responsibility to the Office of the Rubber Replanting Aid Fund to build the Rubber Plantation Aid Fund Co-operation plants (RCOPs), each has a capacity to produce 2 tons of smoked rubber sheets per day. The initiation of these plants aimed to encourage local rubber farmers to form a co-operative group which would help increase production efficiency and improve bargaining position with the rubber traders. However, in the past years there have been many RCOPs suffering from loss in profit that pushed them out of business. The major reasons are inefficient management, production planning and control, quality control, and analysis and control of production costs. By employing benchmarking technique, this study is aiming to improve the efficiency of production resource management of the RCOPs, which will increase productivity and profit, as well as reduce impact to the environment from their production activities. In the first phase, resource utilization indicators were formulated and data from the previous year (2003) of all 76 RCOPs in Songkhla province were analyzed according to such set indicators. Twenty three RCOPs with good overall performance in each indicator were selected, followed by the detailed field data collection. Specific techniques and good practices from each RCOPs were gathered and analyzed for success factors. In the second phase, the good techniques and practices found were applied to the volunteered RCOPs. These RCOPs then participated in the planning of plant improvement and impler:entation. Data before and after the implementation were gathered for comparison.